Thymoma and thymic carcinoma: a perspective on the NCCN clinical practice guidelines in oncology - Kalhor, Neda; Moran, Cesar A. (Mediastinum; Vol 2 (August 2018): Mediastinum, 2018)
Over the years the issue of classification of thymoma has been discussed without universal agreement. More recently, the issue of staging has become an important topic of discussion and attempts to correlate these tumors with more novel staging systems have been reported. However, for most pathologists, the diagnosis of thymoma and thymic carcinoma represent two distinct morphological tumors that unfortunately have been staged using similar staging systems as those use for thymomas, even though they have been clearly defined as tumors with different clinical behavior. Some of this generalizations regarding thymoma and thymic carcinoma are becoming widespread to the point that in the latest NCCN clinical guidelines in oncology for thymoma and thymic carcinoma, the authors of such guidelines have basically grouped these two tumors almost as equal, which not only is worrisome but also it may be just plain incorrect. The views presented in this review will attempt to highlight some of the critical areas where there seems to be an issue in understanding these two different tumors. However, our focus will be in the diagnosis and staging of thymoma and thymic carcinoma and not in the treatment modalities or diagnostic imaging that may be used in the diagnosis of mediastinal tumors.